Microbial responses to oxidative stress - Law, Daniel Zhen Yi. (2010)
A host’s defense system utilizes reactive oxygen species to damage bacterial cells. This project was commissioned to investigate the oxidative stress-induced changes in gene expression levels and how these transcriptional changes result in changes in bacterial phenotypes. Experiments were carried out mainly on two strains of Escherichia Coli, namely the wild-type W3110 Strain and the mutant LW12 Strain. The mutant E.coli is a strain which has its luxS gene (responsible for AI-2 production) deleted. The deletion resulted in a slower growth rate and subsequent lower metabolite production. The effects of this difference in metabolite production was investigated in a hydrogen peroxide (H2O2) assay followed by a Colony Forming Unit (CFU) counting procedure to determine cell viability in environments with varying oxidative stresses. The metabolites produced by the cells during cell growth were thought to contain substances which could buffer the effects of oxidative stresses. This hypothesis was rigorously tested in the H2O2 array experiment.